VD_FINDINFO ML / 2018 / 89 vom 11. September 2018 - VD Tribunal cantonal (2018)
MAINLEVÉE DÉFINITIVE, COMPENSATION DE CRÉANCES, DÉPENS, CESSION DE CRÉANCECO | 169 al. 2 CO, 80 al. 1 LP, 81 al. 1 LP, 47 LPAv, 111 al. 2 CPC (CH), 432 CPP (CH), 433 CPP (CH)